Understanding the Nature of Cooperation Variability - Toke R. Fosgaard; Lars Gårn Hansen; Erik Wengström (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
We investigate framing effects in a large-scale public good experiment. We measure indicators of explanations previously proposed in the literature, which when combined with the large sample, enable us to estimate a structural model of framing effects. The model captures potential causal effects and the behavioral heterogeneity of cooperation variability. We find that framing only has a small effect on the average level of cooperation but a substantial effect on behavioral heterogeneity and we show that this can be explained almost exclusively by a corresponding change in the heterogeneity of beliefs about other subjects' behavior. Preferences are on the other hand stable between frames.
Keywords: C13; C71; C93; H41; 330; Framing; Public Goods; Internet Experiment; Simulation